Associations between childhood adversity and daily suppression and avoidance in response to stress in adulthood: can neurobiological sensitivity help explain this relationship?. Issue 2 (4th March 2017) - Hagan, Melissa J.; Bush, Nicole; Mendes, Wendy Berry; Arenander, Justine; Epel, Elissa; Puterman, Eli
ABSTRACT: Background and objectives: Although it has been postulated that psychological responses to stress in adulthood are grounded in childhood experiences in the family environment, evidence has been inconsistent. This study tested whether two putative measures of neurobiological sensitivity (vagal flexibility and attentional capacity) moderated the relation between women's reported exposure to a risky childhood environment and current engagement in suppressive or avoidant coping in response to daily stress. Design and methods: Adult women ( N  = 158) recruited for a study of stress, coping, and aging reported on early adversity (EA) in their childhood family environment and completed a week-long daily diary in which they described their most stressful event of the day and indicated the degree to which they used suppression or avoidance in response to that event. In addition, women completed a visual tracking task during which heart rate variability and attentional capacity were assessed. Results: Multilevel mixed modeling analyses revealed that greater EA predicted greater suppression and avoidance only among women with higher attentional capacity. Similarly, greater EA predicted greater use of suppression, but only among women with greater vagal flexibility. Conclusion: Childhood adversity may predispose individuals with high neurobiological sensitivity to a lifetime of maladaptive coping.